Analysis of Spiral Pump Head Based on Water Wheel Parameters - Luntungan, Hengky; Tangkuman, Stenly; Maluegha, Benny Lokombanua (Universitas Sanata Dharma, 2025)
Water supply is a crucial factor for farmers in managing agricultural land, especially those relying on river water sources. The lower position of rivers and the considerable distance from the fields often pose challenges, making water pumps powered by electricity or fuel a common choice, despite their high operational costs. To address this issue, the utilization of renewable energy through the use of a spiral pump powered by a water wheel is proposed. The spiral pump is considered an environmentally friendly technology as it does not require electricity or fossil fuels. This study aims to analyze the head of a spiral pump based on the parameters of an undershot water wheel as preparation for the design of the spiral pump. In this study, a significant decrease in discharge value was observed from a head of 0.5 m up to a head of 3 m; in contrast, from a head of 3 m to 10 m, the discharge value decreased gradually. For small agricultural land or household needs, this spiral pump water wheel would be suitable at a maximum head of 5 m with a discharge value of 0.53 L/s. The results show a negative correlation between the head of the spiral pump and the discharge produced, where an increase in head results in a lower discharge.